HISTORY OF THE FINANCIAL SYSTEM IN UZBEKISTAN - Дусчанов Р.Р. (TARIXIY TADQIQOTLAR, 2026)
The article examines the formation of the financial system in the history of Uzbek statehood, including the oversight of treasury revenues and expenditures beyond taxes and levies. It also analyzes the varying terminology used to denote finance during different ruling dynasties and the distinctive features of the functions assigned to these institutions. In addition, the study traces the historical introduction of the financial and budgetary system into the Turkestan Governor-Generalship.